Simulation Approach Towards Energy Flexible Manufacturing Systems - Beier, Jan.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This authored monograph provides in-depth analysis and methods for aligning electricity demand of manufacturing systems to VRE supply. The book broaches both long-term system changes and real-time manufacturing execution and control, and the author presents a concept with different options for improved energy flexibility including battery, compressed air and embodied energy storage. The reader will also find a detailed application procedure as well as an implementation into a simulation prototype software. The book concludes with two case studies. The target audience primarily comprises research experts in the field of green manufacturing systems. .
Introduction -- Manufacturing systems and variable renewable electricity supply -- Existing approaches in the field of energy flexible manufacturing systems -- Manufacturing system real-time energy flexibility control and improvement -- Manufacturing system real-time energy flexibility control and improvement -- Example application -- Summary, critical review and outlook.
Keywords: Manufactures; Management; Sustainability; Electric power production; Energy policy; Energy and state; Machines, Tools, Processes; Management; Sustainability; Electrical Power Engineering; Mechanical Power Engineering; Energy Policy, Economics and Management